2019
DOI: 10.1002/ptr.6490
|View full text |Cite
|
Sign up to set email alerts
|

Allium vegetables for possible future of cancer treatment

Abstract: Natural resources such as plants are an upright curing option in treating cancers and reducing the side effects of current therapeutic modalities. Allium genus vegetables are of the most interesting herbs in restricting cancers that includes garlic, onions, leeks, chives, and shallots. These plants have been exploited in folk medicine because of their beneficial health effects in improving numerous diseases. The phytochemical analysis of various Allium genus members showed that, to date, 16 species have proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 224 publications
(371 reference statements)
1
27
0
2
Order By: Relevance
“…According to Szychowski et al (2018) aqueous extracts are found to be efficient in several biological activities due to their efficacy to extricate compounds. Results are in accordance with Asemani et al (2019) who reports that allium vegetables such as A. sativum , A. cepa , A. hirtifolium , A. jesidianum and A. porrum are a rich source of phytochemicals such as flavonoids, phenolic acids, alkaloids, saponins and organo sulphur compounds. Zhang et al (2020) has suggested A. sativum as a promising candidate for the treatment of cancer due to the similar active phytocomponents reported in our results.…”
Section: Resultssupporting
confidence: 92%
“…According to Szychowski et al (2018) aqueous extracts are found to be efficient in several biological activities due to their efficacy to extricate compounds. Results are in accordance with Asemani et al (2019) who reports that allium vegetables such as A. sativum , A. cepa , A. hirtifolium , A. jesidianum and A. porrum are a rich source of phytochemicals such as flavonoids, phenolic acids, alkaloids, saponins and organo sulphur compounds. Zhang et al (2020) has suggested A. sativum as a promising candidate for the treatment of cancer due to the similar active phytocomponents reported in our results.…”
Section: Resultssupporting
confidence: 92%
“…The usage of medical herbs dates back to ancient times when they were used to relieve both physical and mental pain, while they are still widely applied and continually investigated nowadays due to their numerous advantages in various fields of medicine. Allium vegetables constitute a group of flowering plants belonging to the Amaryllidaceae family, which are currently one of the most prevalently used in medicine [1]. The Amaryllidaceae family consists of more than 850 different species, among which garlic (Allium sativum), onion (Allium cepa), leeks (Allium tuberosum), chives (Allium schoenoprasumum), and shallot (Allium hirtifolium) are most often used for medical purposes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Лук содержит витамины А, В1, В2, С, никотиновую и пантотеновую кислоты, является богатым источником диетических флавоноидов, а так же F, P, Са, Fe, Al, Cu, Zn, Mn. Лук обладает высокой антиоксидантной активностью, содержит эндогенные метаболиты, имеющие защитные эффекты против развития сердечно-сосудистых и неврологических заболеваний, рака и др., которые вызваны окислительным стрессом (Upadhyay, 2016;Miri, Roughani, 2018;Asemani et al, 2019).…”
Section: Introductionunclassified